1971
DOI: 10.1029/wr007i005p01338
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Thomas and Fiering Model to Skewed Hydrologic Data

Abstract: An inconsistency is noted in the transformation to modify random normal variates to random skewed variates used in the Thomas and Fiering hydrologic generation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 3 publications
0
10
0
1
Order By: Relevance
“…In hydrology, log-normal and gamma distributions have been the most popular; the gamma variable being generated by a X 2 variable and the Wilson and Hilferty (1931) transformation. However, McMahon and Miller (1971) showed that this was poor for skewness in excess of two, as it often is, and Kirby (1972) suggested a modified transformation for Pearson Type III distributions. However, Bernier (1970), Weiss (1973a, b) and Lewis (1975, private communication) have obtained the exact distribution of {St} which ensures {Vi} has a gamma distribution; solutions in other cases are awaited.…”
Section: A T+1 Atmentioning
confidence: 99%
“…In hydrology, log-normal and gamma distributions have been the most popular; the gamma variable being generated by a X 2 variable and the Wilson and Hilferty (1931) transformation. However, McMahon and Miller (1971) showed that this was poor for skewness in excess of two, as it often is, and Kirby (1972) suggested a modified transformation for Pearson Type III distributions. However, Bernier (1970), Weiss (1973a, b) and Lewis (1975, private communication) have obtained the exact distribution of {St} which ensures {Vi} has a gamma distribution; solutions in other cases are awaited.…”
Section: A T+1 Atmentioning
confidence: 99%
“…Historically, most of the questions raised regarding the TF approach have concerned the case of the AR(1) model and the range of attainable skewness coefficients [20,38,43]. This was mainly due to the use of Wilson-Hilferty transformation which was used for generating Gamma or Pearson type-III RVs [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, this technical issue is out of interest, since such RVs can be easily generated with high accuracy by modern random number generators which are available in almost every programming language (e.g., R, MATLAB, etc.). Additionally, we note that McMahon and Miller [20] reported that Thomas and Burden [18] and Fiering [5] tested their approach for skewness values ranging in (−0.5, 1.0). This work focused on the effect of using Pearson type-III white noise in AR(1) models and we show that this approach leads to unrealistic dependence patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The general gamma distribution is a three-pai'ameter distri- where G, is the desired skew coefficient of •t and where r/t is a normal independent process of mean zero and variance one, resulting in an independent process with mean zero, variance one, and skew coefficient G•. McMahon and Miller [1971] showed that this transformation is inaccurate for Gx >• 2. Kirby [1972] provided a modification of the transformation which gives good results for Gx •< 10.…”
Section: Gamma Distributionmentioning
confidence: 99%